2002
DOI: 10.1037/1089-2699.6.4.291
|View full text |Cite
|
Sign up to set email alerts
|

A review and integration of classification systems relevant to teams in organizations.

Abstract: Along the same line, Goodman, Ravlin, and Schminke (1987) remarked, I would like to express my appreciation to Kathleen Brandt and Laura Clayton for their help in reviewing the literature, Bill Rogers for his insightful comments on several earlier versions of this article, and Julie Devine for her editorial assistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
182
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(190 citation statements)
references
References 28 publications
(58 reference statements)
0
182
0
5
Order By: Relevance
“…Thus, we believe this task is representative of an interdependent team task and that our study generalizes to short-term project teams whose members work interdependently on novel tasks within a fixed period of time (Devine, 2002;Hollenbeck, Beersma, & Schouten, 2012). Observation of our participants also suggested that they found the task psychologically engaging and the financial incentives motivating based on their enthusiasm regarding the task and the concerns they expressed about the rewards.…”
Section: Goal Setting In Teams 26mentioning
confidence: 86%
“…Thus, we believe this task is representative of an interdependent team task and that our study generalizes to short-term project teams whose members work interdependently on novel tasks within a fixed period of time (Devine, 2002;Hollenbeck, Beersma, & Schouten, 2012). Observation of our participants also suggested that they found the task psychologically engaging and the financial incentives motivating based on their enthusiasm regarding the task and the concerns they expressed about the rewards.…”
Section: Goal Setting In Teams 26mentioning
confidence: 86%
“…In contrast to perceiving a task as repetitive or routine, innovative tasks are perceived as highly novel, low-structured, and highly complex (De Dreu and Weingart 2003;Devine 2002;Hoegl et al 2003), which is argued to trigger team learning behaviors (Edmondson et al 2003). Perceiving task novelty as high could stimulate team members to collectively develop new solutions instead of adhering to the status quo (Hoegl et al 2003).…”
Section: The Role Of Task Perception On Team Learning Behaviormentioning
confidence: 99%
“…Innovative tasks are defined here as highly novel, complex, and low-structured (De Dreu and Weingart 2003;Devine 2002;Hoegl et al 2003). Fullan (2010) suggests that working together on an innovative task potentially offers university teachers the opportunity of combining multiple inputs in identifying the need for innovation, developing ownership, and designing, implementing, and evaluating solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Modern organizations heavily rely on teamwork to accomplish a variety of tasks ranging from production to strategic decisions (Devine 2002), and teamwork skills become a valuable asset for employees in most industries (Burch and Anderson 2004). Higher education institutions have responded to this trend and extensively use group project work (collaborative and cooperative learning) as a pedagogical tool (Davies 2009;Graen et al 2006).…”
Section: Introductionmentioning
confidence: 99%